MEMAHAMI TEORI BELAJAR BEHAVIORISTIK DAN IMPLEMENTASI DALAM PEMBELAJARAN - Peri Gunawan Peri; Rika Siti Karimah (MGMP PAI Jawa Barat, 2022)
This study aims to find out the theory of behavioristic learning according to experts, know the advantages and disadvantages of behavioristic theory and be able to understand and know the application of behavioristic theory in the learning process. This research uses Library Research, which is in the process of collecting data by looking for literature collections and from research that has previously been carried out. Behavioristic theory appeared in the 1960s and 1970s by Thorndike, Pavlov and Skinner. Behavioristic theory emphasizes the behavior of learners as evidence of having followed the learning process. Learning is the interaction between stimulus and response. Behavioristic theory has the advantage of accustoming students to be conscientious, independent, and think critically. Meanwhile, the shortcomings of behavioristic theory are restrictions on student productivity and imagination, students are passive, and have the potential to cause punishment both verbal and physical. In general, learning activities based on behavioristic theory must go through learning steps, including determining learning objectives, analyzing the classroom environment, determining learning materials, dividing learning materials into small parts, presenting material, providing stimulus, observing student responses, providing reinforcement, providing new stimuli, providing punishment, and evaluating the learning process.